Confident teens: how to raise a positive, confident and happy teenager - Lindenfield, Gael (London: Thorsons, 2001)
A Lindenfield guide to helping teenagers and young adults stay confident and feel good about themselves. Teens today need more help than ever. Being expected to grow up quickly; facing the problems of immense peer pressure; facing exam challenges ' and getting to grips with the many changes and events of the teenage years can be exceedingly daunting. Confidence levels and the grown-up personality are moulded in your teens, and setbacks around this time can seriously impact on self-esteem in later life. However, confident teenagers should grow up to become confident people and this book shows how parents can best understand, support, befriend and give confidence to their teenage child. Written for adults, this is a candid and sympathetic guide which will help parents to be prepared for the roller coaster teenage years. Why it's important to acknowledge that times have changed.- Why experimentation is important to your teen's identity and well being.- How to nurture your child through a bad patch.- How to help your child develop healthy independence.- What teenagers worry about. Where to start with sexuality, drugs, work, college and the future. The book includes tips on how to deal with typical teenager scenarios and has a series of Golden Rules for parents to follow. Note that it has not been possible to include the same picture content that appeared in the original print version
Includes bibliographical references and index.
Keywords: Adolescence; Parent and teenager; Self-confidence in adolescence; Self-esteem in adolescence; Self-resilience in adolescence